Literature Review: Alcohol Content in Traditional Drinks in Indonesia - Fitroh Annisaul Mubarokah; Jumiati; Putri Raniyatu; Teguh Setiawan Wibowo (Journal of International Multidisciplinary Research, 2024)
Traditional Indonesian alcoholic drinks are drinks that contain alcohol and have a cultural role in Indonesian society. Not only in Indonesia but various countries around the world also make alcoholic drinks a part of their culture. As in China, alcohol or arak is used as medicine, cooking spices, and also in ceremonial events. Meanwhile, Japan uses arak as a dish at formal meetings or celebrations. Several regions in Indonesia have traditional drinks that contain alcohol and these drinks are always present at every celebration, traditional ceremony, thanksgiving event, death ceremony, or welcoming guests. In this article, we will discuss the impact of alcohol use and the alcohol (ethanol) content in various traditional alcoholic drinks in Indonesia.